Rancang Bangun Alat Pengering Pakan Ikan dengan Sistem Pemanas Konveksi Paksa - Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
The natural drying proses that is required to dry pellet fish have some shortages, such as : a long time and need some time reversal process. Because of this dryer is designed using artificial heating system with forced convection. Dryers is designed for the capacity of 2 kg per hour. It has components : dryer room, plats, space heating, hot conduit, a chanel for the fan and the evaporation air stream through all the components. LPG is used as fuel and heating burner is completed with an on off system controler. To dry 2 kg of fish pellet with 30% to 15% water content required 5 pieces of plats 30 cm x 30 cm dry air flowrate 17 m3/menit. After drying, the water can be evaporated from pellet was 0,3 kg. In one-time process dryer can produce 1,7 kg pellet. From the test conducted, the time required to dry 2 kg of fish pellet only takes 32 minutes. With room temperature is set 60-80 oC.